Inclusion of disability in primary healthcare facilities and socioeconomic inequity in Brazil - Kuper, Hannah; Pinto, Alexandro Rodrigues; Silva, Everton Nunes da; Barreto, Jorge Otávio Maia; Powell-Jackson, Tim (Revista de Saúde Pública, 2024)
OBJECTIVE: To describe disability-related performance and inequality nationwide in Brazil, and the changes that took place between 2012 and 2019 after the introduction of Programme for Improving Primary Care Access and Quality (PMAQ). METHODS: We derived scores for disability-related care and accessibility of primary healthcare facilities from PMAQ indicators collected in round 1 (2011–2013), and round 3 (2015–2019). We assessed how scores changed after the introduction of PMAQ. We used census data on per capita income of local areas to examine the disability-specific care and accessibility scores by income group. We undertook ordinary least squares regressions to examine the association between PMAQ scores and per capita income of each local area across implementation rounds. RESULTS: Disability-related care scores were low in round 1 (18.8, 95%CI 18.3–19.3, out of a possible 100) and improved slightly by round 3 (22.5, 95%CI 22.0–23.1). Accessibility of primary healthcare facilities was also poor in round 1 (30.3, 95%CI 29.8–30.8) but doubled by round 3 (60.8, 95%CI 60.3–61.3). There were large socioeconomic inequalities in round 1, with both scores approximately twice as high in the richest compared to the poorest group. Inequalities weakened somewhat for accessibility scores by round 3. These trends were confirmed through regression analyses, controlling for other area characteristics. Disability-related and accessibility scores also varied strongly between states in both rounds. CONCLUSIONS: People with disabilities are being left behind by the Brazilian healthcare system, particularly in poor areas, which will challenge the achievement of universal health coverage.